2015 IEEE 12th International Symposium on Biomedical Imaging (ISBI) 2015
DOI: 10.1109/isbi.2015.7164105
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-isometric length parameterization of cortical sulci: Application to handedness and the central sulcus morphology

Abstract: We present in this paper a method to perform a length parameterization of cortical sulcus meshes. Such parameterization allows morphological features to be localized in a normalized way along the length of the sulcus and can be used to perform population studies and group comparisons. Our method uses the second eigenfunction of the Laplace-Beltrami operator, and the resulting parameterization is quasi-isometric. The process is validated on the central sulci of a set of subjects and its efficiency is demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…While cortical folds and sulcal parameters can be affected by genetics and environmental factors, there is consistent similarity in the patterns of folds and sulci of healthy individuals. As shown in a study of handedness [4], the central sulcus starts and ends in similar locations and has dips in similar positions along the sulcal path. Subtle abnormalities in cortical folding patterns can be indicative of diseases such as ADHD, schizophrenia, autism or bipolar disorder [6], [7].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…While cortical folds and sulcal parameters can be affected by genetics and environmental factors, there is consistent similarity in the patterns of folds and sulci of healthy individuals. As shown in a study of handedness [4], the central sulcus starts and ends in similar locations and has dips in similar positions along the sulcal path. Subtle abnormalities in cortical folding patterns can be indicative of diseases such as ADHD, schizophrenia, autism or bipolar disorder [6], [7].…”
Section: Introductionmentioning
confidence: 90%
“…Cortical folding parameters such as sulcal depth can be a marker of functional specificities or developmental pathologies [2], [3]. Some studies have shown that sulcal depth varies for right handed and left handed participants in the central sulcus [4], [5]. While cortical folds and sulcal parameters can be affected by genetics and environmental factors, there is consistent similarity in the patterns of folds and sulci of healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…A sulcal parameterization process was then applied to the left and right central sulci of each subject and depth was measured at each position along the sulcus, which resulted in a depth curve for each central sulcus, as described in [5, 6]. This method detects the dorsal and ventral extremities and provides a smooth isometric parameterization that, for every point on the sulcus, indicates its relative position between the two extremities [5]. For each position within [0 100], the depth at this position is estimated by measuring the length of the corresponding isoparametric lines.…”
Section: Methodsmentioning
confidence: 99%
“…We isometrically parameterized the PreCG and PoCG crest lines, in an intrinsic manner, as proposed in (Coulon et al 2015), from the ventral (coordinate 0) to the dorsal end (coordinate 100). For a given streamline, its pre-central (resp.…”
Section: Short Structural Connectivity Profiles Of the Csmentioning
confidence: 99%